Professor polivalente: reflexões para um caminho de incertezas - Vacilotto, Eder (2020)
The multipurpose teacher actually is a professional graduated in Pedagogy and is part of their scope to act in the primary education. Within this context that this dissertation presents a panorama regarding the professional practice, a dialogue between reflective reports of primary education and features of Constitution, in order to raise interesting possibilities to improve the education of these professionals. Following this journey, this dissertation is divided in four quarters, similar to a school year in a primary school. In the first quarter, a diagnose of the multipurpose teacher formation, describes their responsibilities and problematize from the National Curricular Guidelines against to theorical and practice context, under the perspective of Freire (1997) and Fortunato (2018). The second quarter is based on the Romanovsky and Ens (2006) theory, on the State of Knowledge having the last 5 years as a criteria, which presents possible directions in the research about the formation of this professional. The third quarter brings the notion of schooling and its influence in the constitution of the multipurpose teacher identity, with the theorical input of Snyders & Lopez (2009), Pimenta (2012), Freire (1982), Imbernón (2009), Tardiff and Lessard (2017), among others, that presents the perspective of the school environment about this professional. The multipurpose teacher trajectory is built in an uncertainties path. In the fourth quarter is identified possibilities and formative journey that interweave didactic discipline, initial formation and the current continuing education, which in the daily school routine allow advances in pedagogical conditions. The research identifies the weakness of the multipurpose teacher identity but understand that the practice can be an enlightening route in the formation of this professional. The formation can present some uncertainties path, but being at school, in this learning space, formative journey is presented.